Biotic resistance to tropical ornamental invasion. (20th January 2016) - Bufford, Jennifer L.; Lurie, Matthew H.; Daehler, Curtis C.
Summary: We examined invasive, casual (found occasionally outside cultivation) and non‐invasive (found only in cultivation) species to investigate the role of species traits and two forms of biotic resistance (plant neighbours and herbivores) in limiting invasion in Hawaiian lowlands. Seeds of 21 species of common woody ornamentals from three plant families (Acanthaceae, Apocynaceae, Bignoniaceae) that are non‐invasive, casual or invasive in Hawai'i were outplanted at two field sites. We measured germination of seeds and growth and survival of seedlings for 1 year in plots with and without neighbours from the naturally assembled community. The presence of neighbours reduced survival in some species, mostly non‐invasive or casual species, and completely excluded two non‐invasive species from community plots. Damage from the existing community of herbivores was correlated with lower survival in the Acanthaceae and Bignoniaceae, but not the Apocynaceae. Non‐invasive and casual species had lower survival and growth rates than invasive species and lower photosynthetic rates in the presence of neighbours than invasive species. Non‐invasives without neighbours also had lower specific leaf area than invasives and casuals. We found evidence for barriers to invasion in some non‐invasive and casual species, including low growth rate, low survival, or low survival in the presence of neighbours. By contrast, five of the six invasives flowered and three began setting fruit within the duration of the experiment, as did one of the casual species. Synthesis . Our research demonstrates biotic resistance, presumably as a result of competition. Neighbouring plants reduced survival and growth for most species. For non‐invasive species with low survival and growth even without competition from neighbouring plants, this resulted in complete exclusion from community plots or such low growth rates that exclusion over longer time frames was likely. We also provide evidence for traits‐based barriers to invasion in non‐invasive and casual species. However, no single barrier to invasion was shared across all non‐invasive and casual species. Abstract : Biotic resistance and species traits limit invasion of tropical ornamental plants in Hawaiian lowlands. By monitoring seedlings of invasive, casual and non‐invasive species, we demonstrated biotic resistance due to plant neighbours, but not herbivores. We found evidence for barriers to invasion in some non‐invasive and casual species, including low growth rate and survival, especially in the presence of neighbours.